Pengaruh Kualitas Pelayanan dan Pengalaman Pelanggan Terhadap Kepuasan Pelanggan pada BNI Kcu Jl. Perintis Kemerdekaan Bandung - Dhea Octaviani; Dadan Abdul Aziz Mubarok (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Escalating competition within the financial services industry pushes banks to look beyond product-based advantages and instead pay closer attention to how services are delivered and perceived by customers. This study analyzes the degree to which service quality and customer experience determine the satisfaction levels of clients at BNI KCU Perintis Kemerdekaan. Employing a quantitative survey-based approach, a total of 105 customers were recruited through purposive sampling. Data were executed via Partial Least Squares Structural Equation Modeling (PLS-SEM) utilizing the SmartPLS 4.0 software. The empirical outcomes demonstrate that service quality exerts a positive and significant effect on client satisfaction. In a similar vein, customer experience also has a positive and significant impact exhibiting an even stronger effect compared to service quality. The coefficient of determination (R-square) reaches 0.575 revea that both variables jointly account for 57.5% of the variance in client satisfaction. Ultimately, this research confirms that elevating service quality while simultaneously optimizing customer experience represents a strategic imperative for banks seeking to optimize satisfaction